EFFECT OF ETHICS AND WORK EXPERIENCE ON THE WORK ACHIEVEMENT OF HIGH SCHOOL TEACHERS IN BATAM CITY - Adnan Suhardis (Universitas Batam, 2020)
The teacher is an educational component that is very important in determining the success of education to achieve its goals. The teacher is the main actor who is directly related to the teaching and learning process (KBM) in the classroom. The factors that gain a teacher's performance are ethics and experience that become benchmarks in increasing or decreasing work performance. This study aims to analyze the partial and simultaneous influence of ethics and experience variables on work performance. The data analysis technique uses multiple linear regression analysis techniques with two independent variables and one dependent variable. The results of the analysis obtained that the t-count value of work ethics (X1) was 4.126> t table 2.006, and the value of Sig. <0.05 (0.00 <0.05), so it can be concluded that work ethic (X1) has a significant effect in a positive direction on work performance. The t-count value of work experience variable (X1) is 4.126> t table 2.006, and the Sig. <0.05 (0.00 <0.05), so it can be concluded that work experience (X1) has a significant effect in a positive direction on work performance. F count value of 78.546 with a significant level of 0.000. Furthermore, how to obtain the Ftable value with a significant level of 95% (Î± = 0.05) is to use the formula (F table = F (K: n-k) = F (3:69) = 2.78) so the F table value is 2.78 . It can be concluded that the F count value is 78.546> Ftable value is 2.78. This means that simultaneously there is a significant influence between work ethics and work experience variables on the dependent variable work performance (Y).